State Responsibility for Access and Availability of Patented Drugs for Public Health - Lidya Shery Muis; Rahmi Jened; Nurul Barizah; Go Chin Tjwan (Yuridika, 2023)
Article 28H and Article 34 of the 1945 Constitution of the Republic of Indonesia stipulate that fulfilling the health rights of Indonesian citizens is the responsibility of the state. Human rights require that individuals have access to the availability of medicines in society. The high price of medicines, especially patent medicines, results in limited access and availability of essential medicines. This study uses normative legal research methods, with a statutory approach, and a conceptual approach. The purpose of this study is to examine and analyze the state's goals in fulfilling the right to health as a human right by the state as well as access and availability of patented drugs to fulfill the right to health. In addition to ensuring the availability of complete medicines in sufficient quantity, quality, affordable and easily accessible to the public, the government is also responsible for protecting the rights of inventors as long as the drugs are still under patent protection. To balance these two rights, the government plays the role of provider, regulator, entrepreneur and umpire.